2005
DOI: 10.1248/cpb.53.503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compression on Interaction between 1,4-Dihydropyridine Compounds and Lactose Monohydrate

Abstract: 1,4-Dihydropyridine type compounds such as Nifedipine and Nicardipine hydrochloride have antihypertensive activity, which are frequently used as a calcium channel antagonist. Especially, manidipine dihydrochloride and benidipine hydrochloride have the characteristics of more potent and longer acting than the other 1,4-dihydropyridines, which have been developed in the earlier time. 2,3)The drug molecules commonly have polymorphs and/or solvate forms whose solubility, stability and also bioavailability are well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…5) The endothermic peaks at 170°C were observed for all particle sizes of Lac and their area increased with the increase in compression force not only for Lac25 6) but also for Lac75 and Lac125. These results show that the interaction between Man and Lac during thermal treatment was accelerated by the mechanical energy of compression.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…5) The endothermic peaks at 170°C were observed for all particle sizes of Lac and their area increased with the increase in compression force not only for Lac25 6) but also for Lac75 and Lac125. These results show that the interaction between Man and Lac during thermal treatment was accelerated by the mechanical energy of compression.…”
Section: Resultsmentioning
confidence: 89%
“…1,2) We described the dissolution behaviors of the anhydrate and monohydrate forms of Ben. 3,4) We also found that an interaction occurred during differential scanning calorimetry (DSC) measurements of physical mixtures of Man or Ben with lactose monohydrate (Lac), but no interaction was observed with lactose anhydrate.5) The water of crystallization in Lac was clearly participated in this interaction. Moreover, we investigated the effects of compression on this interaction and found that it was accelerated by compression and related to disruption of the Lac crystal structure.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Tablet manufacturing process produces thermal and mechanical energy which possibly results in physical interaction amongst components used (Hosaka et al, 2005). During tablet compression, interaction can undergo between active substances, active substance with excipient, or between excipients.…”
Section: Introductionmentioning
confidence: 99%